Kickboxing sparring /c Justyn Billingham - Billingham, Justin (The Crowood Press Ltd, 2009)
Presents sparring drills for various levels. This book shows how to warm up correctly to reduce the risk of injury, how to achieve improved flexibility, and how to develop the box side split and front-split stretch